2019
DOI: 10.1177/0734282919875639
|View full text |Cite
|
Sign up to set email alerts
|

The Italian Version of the State-Trait Cheerfulness Inventory Trait Form: Psychometric Validation and Evaluation of Measurement Invariance

Abstract: The State-Trait Cheerfulness Inventory–Trait Version (STCI-T60) measures the temperamental basis of sense of humor involving theoretically derived personality dispositions of cheerfulness, seriousness, and bad mood. The reliability and validity of the newly developed STCI-T60 Italian version were assessed in a sample of Italian speakers ( N = 683). Proper fit for a three-dimensional factor structure observed in previous studies was replicated and each factor demonstrated acceptable internal consistency and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…The three factors were clearly identified as the three theoretically expected factors of cheerfulness (1), seriousness (2), and bad mood (3), in line with other recent findings on the pilot version of the STCI-T <60> (see Lau et al, 2018 ). All items loaded highest on their theoretically expected factor and no important second loadings occurred, see Table 10 .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The three factors were clearly identified as the three theoretically expected factors of cheerfulness (1), seriousness (2), and bad mood (3), in line with other recent findings on the pilot version of the STCI-T <60> (see Lau et al, 2018 ). All items loaded highest on their theoretically expected factor and no important second loadings occurred, see Table 10 .…”
Section: Resultssupporting
confidence: 88%
“…For trait bad mood, the exact opposite pattern was found. For trait seriousness, a positive correlation to resilience was reported (Lau et al, 2018 ).…”
Section: Validationmentioning
confidence: 97%
“…State-Trait Cheerfulness Inventory—Trait Version (STCI-T60) [ 32 ], Italian version [ 43 ] is a multidimensional measure that assesses latent traits of cheerfulness, bad mood, and seriousness. Research has shown that these traits are linked with psychological well-being, positive affect, and emotion regulation.…”
Section: Methodsmentioning
confidence: 99%
“…First, we used the item parceling technique. While numerous studies have defended this methodology from either a theoretical or empirical perspective (Lau, Chiesi, Hofmann, Ruch, & Saklofske, 2020; Little, Rhemtulla, Gibson, & Schoemann, 2013; Martin et al, 2010), using parcels may obscure sources of sample variance (Little et al, 2013). Future studies may explore the possibility of item-level analysis of multilevel statistics attitude data using categorical data analytical approaches.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%